Assessment of the efficacy of a new complex antisensitive skin cream. (22nd January 2018) - Wang, Yinjuan; Viennet, Céline; Jeudy, Adeline; Fanian, Ferial; He, Li; Humbert, Philippe
Summary: Background: Sensitive skin is frequently complaint in dermatology consultation with cutaneous manifestations such as stinging, redness, dryness, and burning sensation that affect the quality of life. Its pathogenesis is mainly related to dysfunction of neurosensory, skin barrier, and also immune activity. The treatment is generally based on continuous and topical therapy by nonirritating complex. Objective: To evaluate the antisensitive function of a new complex cream composed by Yunnan Portulaca oleracea extract, Prinsepia utilis oil, beta‐glucan, and sodium hyaluronate extracted from mushroom. Methods: A randomized double‐blind and self‐control study was conducted on 20 selected volunteers with sensitive skin. Subjects applied the test cream to 1 side of the face, and the control cream (tolerance‐extreme cream) to the other side of the face, twice daily over 28 days. Evaluations were performed at baseline and at 28 days. Expert clinical grading of facial skin including dryness, roughness, desquamation, and erythema was assessed. Subject self‐assessment questionnaires, digital photography and noninvasive bioinstrumentation of hydration, transepidermal water loss, lipid index, skin texture, and wettability were also included in the study. Results: Products were well tolerated. For all parameters studied, no significant difference was observed between test and control creams. Results showed that test cream provided a statistically significant improvement in clinical grading scores for dryness, roughness, and erythema at 28 days compared to baseline. In addition, statistically significant improvement of skin hydration and texture parameters (eg, smoothness and roughness) was demonstrated. Volunteers' questionnaire revealed self‐perceived benefits consistent with expert visual grading. Conclusion: This study confirmed the effectiveness and tolerance of the new complex cream in subjects with sensitive skin. The test cream could serve as a daily care moisturizer for face.